Spatial inequality of shopping opportunities under the boom of express deliveries in China. (April 2023) - Wu, Zhaoping; Yang, Guofu; Chen, Yi; Du, Yuanyuan; Liu, Shun; Wu, Bijie; Ge, Ying; Chang, Jie
Highlights: The number of express delivery outlets is growing faster than the number of traditional shops. The net ecosystem services provided by express delivery outlets are 3-fold those of shops. The spatial distribution of express delivery outlets is wider and more equal than that of shops. Online shopping reduces the spatial inequality of shopping opportunities by 35%. Spatial inequality declined with the increase of city's economic level and population size. Abstract: The orderly spatial structure of cities promotes city vitality and human well-being. The spatial mismatch between traditional shops and population causes spatial inequality in shopping opportunities along urban‒rural gradients. This spatial inequality has been deconstructed. The rapid expansion of express delivery outlets linked to online shopping reduces the spatial inequality of shopping opportunities to an unknown degree. This study focused on the spatial patterns of shops and express delivery outlets in cities. The Gini coefficient was used to quantify the spatial inequality of shopping opportunities in 18 Chinese cities. This study further compared the ecosystem services of the two types of shopping facilities. The results show that (1) the net ecosystem services provided by express delivery outlets are 3-fold those of shops; (2) the environmental impact of online shopping are lower than those of traditional shopping; (3) express delivery outlets show more spatial dispersion than shops; (4) the spatial inequality of shops is higher than that of express delivery outlets; and (5) the supplement of express delivery outlets to shops reduces spatial inequality by 35%. These findings show that online shopping promotes ecosystem services, reduces the spatial inequality of city structure and improves human well-being and the sustainability of cities. Graphical abstract: Image, graphical abstract